A Thorough Investigation of Code Obfuscation Techniques for Software Protection - Kumar, Krishan; Kaur, Prabhpreet (International Journal of Computer Sciences and Engineering, 2015)
The Process of reverse engineering allows attackers to understand the behavior of software and extract the proprietary algorithms and key data structures (e.g. cryptographic keys) from it. Code obfuscation is the technique is employed to protect the software from the risk of reverse engineering i.e. to protect software against analysis and unwanted modification. Program obfuscation makes code harder to analyze. In this paper we survey the literature on code obfuscation. we have analyze the different obfuscation techniques in relation to protection of intellectual property. At the last, we are purposing suggestion to provide protection from both the static and dynamic attacks.